COVID-19 associated with pulmonary aspergillosis: A literature review - Lai, Chih-Cheng; Yu, Weng-Liang (Journal of microbiology, immunology and infection, 2021)
Bacterial or virus co-infections with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have been reported in many studies, however, the knowledge on Aspergillus co-infection among patients with coronavirus disease 2019 (COVID-19) was limited. This literature review aims to explore and describe the updated information about COVID-19 associated with pulmonary aspergillosis. We found that Aspergillus spp. can cause co-infections in patients with COVID-19, especially in severe/critical illness. The incidence of IPA in COVID-19 ranged from 19.6% to 33.3%. Acute respiratory distress syndrome requiring mechanical ventilation was the common complications, and the overall mortality was high, which could be up to 64.7% (n = 22) in the pooled analysis of 34 reported cases. The conventional risk factors of invasive aspergillosis were not common among these specific populations. Fungus culture and galactomannan test, especially from respiratory specimens could help early diagnosis. Aspergillus fumigatus was the most common species causing co-infection in COVID-19 patients, followed by Aspergillus flavus. Although voriconazole is the recommended anti-Aspergillus agent and also the most commonly used antifungal agent, aspergillosis caused by azole-resistant Aspergillus is also possible. Additionally, voriconazole should be used carefully in the concern of complicated drug–drug interaction and enhancing cardiovascular toxicity on anti-SARS-CoV-2 agents. Finally, this review suggests that clinicians should keep alerting the possible occurrence of pulmonary aspergillosis in severe/critical COVID-19 patients, and aggressively microbiologic study in addition to SARS-CoV-2 via respiratory specimens should be indicated.